Biracial Asian Americans' Mental Health on a Christian College Campus: A Preliminary Report on the Role of Racial-Ethnic Identities and Racial Invalidation - Law, Josephine P. (Journal of psychology and christianity, 2021)
Biracial individuals have unique experiences that shape their identity and, subsequently, their mental health. We examined biracial Asian Americans at a Christian university, studying the relationship between racial-ethnic identity, racial invalidations, and mental health. Our sample consisted of undergraduate students that identified as biracial Asian American (N = 57). We predicted that racial-ethnic identity would be correlated with positive mental health (Hypothesis 1) and that experiencing racial invalidations would be correlated with negative mental health (Hypothesis 2). Participants completed an online survey containing demographic questions and measures related to the study variables. Hypothesis 1 was partially supported, as a stronger Asian identity was associated with higher life satisfaction. Experiencing racial invalidations was associated with depression and anxiety, largely supporting Hypothesis 2. These findings indicate the importance of studying biracial Asian Americans' experiences, especially on Christian campuses that intend to promote an inclusive environment for all students. Further research should continue to consider other identities within the biracial and multiracial category and their related experiences.